Development of mesoporous bioactive glass‐containing macroporous titanium for controlled release of antimicrobial drugs. Issue 3 (6th October 2021) - Kamarudin, Nur Hidayatul Nazirah; D'Haeyer, Camille; Thevissen, Karin; Braem, Annabel
Abstract: Biofilm‐associated infections pose a serious threat to the long‐term survival of metal‐based bone implants, which can potentially be resolved by the controlled delivery of antimicrobial agents locally at the implant surface. Mesoporous bioactive glasses (BAGs) are multifunctional materials able to combine bone‐bonding properties with such a drug release functionality. Here, we propose for the first time to modify a macroporous Ti implant material with an antimicrobial‐releasing BAG phase. The feasibility of a sol‐gel synthesis route, including the structure‐directing agent (SDA) Pluronic F127, and its effect on the mesoporous structure and concomitant drug release performance was evaluated. Mesopore sizes ranged from 3.4 nm for SDA‐free to 3.7 nm for SDA‐derived BAG, thereby both enabling configurational diffusion of the antiseptic chlorhexidine (CHX), but the latter showed a more narrow pore size distribution leading to a slower, more controlled release. Adjusting the feed concentration allowed fine‐tuning the daily CHX release through the SDA‐derived Ti/BAG composite to 1.4 μM. Even though just below the biofilm inhibitory concentration, this daily release rate was sufficient to effectively prevent Streptococcus mutans biofilm formation on the surface of the material. This proof‐of‐concept for a temporary antimicrobial‐releasing bioceramic surface modification on Ti can be of interest for orthopedic implants.